Successful Treatment of Refractory Palmoplantar Pustular Psoriasis With Apremilast: A Case Series - Ständer, Sascha; Syring, Felicia; Ludwig, Ralf J.; Thaçi, Diamant (Frontiers in Medicine, 2020)
Introduction: Palmoplantar pustular psoriasis (PPPP) is a debilitating inflammatory skin disorder of the palms and soles that poses a high burden on affected patients. Satisfactory treatment response is rarely achieved using current treatment options, including topical corticosteroids, psoralen-UVA, systemic anti-inflammatory drugs and even novel biologic substances. However, little is known about a potential benefit of the PDE4 inhibitor apremilast in treatment of refractory PPPP patients. We here aimed to evaluate the efficacy and safety of apremilast in PPPP patients. Patients and methods: Four patients with severe (PGA=3) and two with very severe (PGA=4) and treatment refractory PPPP [mean age (yearsSD): 56,2,  15,6] were included in this study. Five patients had a concomitant psoriatic arthritis (PsA). Prior to apremilast administration, topical corticosteroids, psoralen-UVA and several systemic oral and biologic anti-inflammatory treatments were insufficient to improve the skin condition or had to be discontinued due to adverse events. Apremilast was commenced in all patients with a subsequent clinical follow-up over 18 months. Results: Within the first four weeks of treatment, each patients´ symptoms improved as assessed with physician global assessment (PGA) score. Specifically, three months after treatment, four patients revealed a mild PGA score and two were cleared from PPPP. After 18 months of follow-up, four patients had a stable mild PPPP (PGA=1) and two patients discontinued the treatment due to i.) a missing efficacy concerning PsA and ii.) a desire to have a child. Conclusion: Apremilast appears to be an effective and save treatment option in refractory and severely affected PPPP patients.